RESPONS TANAMAN.TOMAT (Solanun lycopersicum) TERHADAP PEMBERIAN PUPUK ORGANIK CAIR (POC) URINE SAPI DAN PUPUK FOSFOR PADA TANAH ANDISOL - Heppy Kardiani Zebua; Irwan Agusnu Putra; Triara Juniarsih (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2023)
Introduction: The purpose of this study was to determine the response of tomato plants (Solanum licopersicum) to the administrationof liquid organic fertilizer cow urine and phosphorus fertilizers on andisol soil. Materials and Methods: This 'research' was carried out in October 2022 – January 2023 in Selayang village, Finish district, with an altitude of 28 meters above sea level. This study used a factorial randomized block design with 2 treatment factors. The firstfactor is cow urine liquid organic fertilizer with Symbol (A) which consists of 2 treatment levels, namely: A0 = (0 ml), A1 = ( 60 ml). The second factor was the application of phosphorus fertilizer symbol (P) which consisted of 4 treatment levels, namely: P0 (without fertilizer), P1 (125kg P/Ha ≈ 1,7gSP-36/polybag), P2 (250kg P/Ha ≈ 3,5 gSP-36/ polybag) dan P3 (375kg P/Ha ≈ 5,2 gSP-36/polybag). Results: The results showed that the treatment of cow urine liquid organic fertilizer (POC) had a very significant effect on the parameters of plant height aged 56 HST, yield and production of tomato plants with the best treatment found in A1 (60 ml). The aplication of phosphorus fertilizer had a significant effect on soil pH and available-P with the best treatment P1 (125kg P/Ha ≈ 1,7 g SP-36/polybag). The interaction of cow urine liquid organic fertilizer (POC) and phosphorus fertilizer had a very significant effect on the yield and production of tomato plants with the best combination treatment A1P1 (60 ml) (125kg P/Ha ≈ 1,7 g SP-36/polybag). Keywords: Liquid Organic Fertilizer, Phosphorus, Tomatoes